2013
DOI: 10.1073/pnas.1303001110
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hexagonal and cubic ice during low-temperature growth

Abstract: From our daily life we are familiar with hexagonal ice, but at very low temperature ice can exist in a different structure--that of cubic ice. Seeking to unravel the enigmatic relationship between these two low-pressure phases, we examined their formation on a Pt (111) substrate at low temperatures with scanning tunneling microscopy and atomic force microscopy. After completion of the onemolecule-thick wetting layer, 3D clusters of hexagonal ice grow via layer nucleation. The coalescence of these clusters crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 42 publications
(46 reference statements)
4
83
0
Order By: Relevance
“…This lower bound is consistent with, but on the high side of, experimentally measured free energy differences of 0.3 − 1.6 meV/H 2 O [7][8][9][10][11][12][13][14][15]. Notably, the experimental value is rather uncertain, mainly because the free energy difference is very small, and because the Ic samples are typically not fully characterised in terms of stacking faults or proton ordering.…”
Section: Resultssupporting
confidence: 77%
“…This lower bound is consistent with, but on the high side of, experimentally measured free energy differences of 0.3 − 1.6 meV/H 2 O [7][8][9][10][11][12][13][14][15]. Notably, the experimental value is rather uncertain, mainly because the free energy difference is very small, and because the Ic samples are typically not fully characterised in terms of stacking faults or proton ordering.…”
Section: Resultssupporting
confidence: 77%
“…Similar double bilayer structures were observed on the prism and basal plane. Similar features and unambiguous signatures of cubic ice spirals were also identified by atomic force microscopy (AFM) and scanning tunneling microscopy (STM) 116 on an ice sample imaged at 145 K.…”
Section: [H1] High Vacuum and Modelling Studiessupporting
confidence: 54%
“…Below about 200 K, however, water may be encountered in the metastable cubic form ice I c (e.g., Hobbs, 1974). Recently, studies using diffraction measurements and numerical simulations showed that samples were not composed of pure cubic ice, but rather exhibited crystalline sequences of cubic ice interlaced with sequences of hexagonal ice (e.g., Hudait et al, 2016;Kuhs et al, 2012;Lupi et al, 2017;Malkin et al, 2015;Shallcross and Carpenter, 1957;Thürmer and Nie, 2013). This ice polymorph has been termed stacking disordered ice I sd .…”
Section: Comparison To Literature Datamentioning
confidence: 99%